Conservation of local resources: The role of kepok banana blossom in supporting breast milk production - Heryani, Sri; Ningrum, Widya Maya; Mukti, Arifah Septiane; Rohmah, Siti (Interdisciplinary International Journal of Conservation and Culture, 2024)
Optimal production of breast milk is essential to support the health and development of babies. One of the efforts that can be made to increase breast milk production is through the nutrition of breastfeeding mothers. This study aims to determine the effect of consumption of banana kepok blossoms on breast milk production. The study was conducted at PMB Midwife Fitri, Ciamis, using a pre-test and post-test design in an intervention group consisting of 15 breastfeeding mothers. The results showed that the consumption of banana kepok blossoms could significantly increase breast milk production, from an average of 54 mL before the intervention to 99 mL after the intervention. These findings provide an alternative to natural ingredients-based nutrition to support breast milk production in breastfeeding mothers.